Effects of temperature on gas exchange, berry and wine composition in two grapevine varieties - Gallo, Agustina Eugenia; Bustos Morgani, Marianela; Fanzone, Martín Leandro; Sari, Santiago Eduardo; Martinelli, Daniela; Lopez Pelegrina, Leandro; Calabrese, Nicolas; Perez Peña, Jorge Esteban; Prieto, Jorge Alejandro (Instituto Nacional de Vitivinicultura de Uruguay, 2025)
Póster y Resumen